STRATEGI KOMUNIKASI BALAI TAMAN NASIONAL TESSO NILO DALAM MENANGANI KONFLIK SOSIAL MASYARAKAT TAMAN NASIONAL TESSO NILLO KABUPATEN PELALAWAN - Bayu Agung Pratama; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research based on social conflict society that occurred in Tesso Nilo National Park (TNNP). Conflict occured because of expansion of the area to 100.000 acres based by letter no 522. Ekbang /6630 date 21 November 2009 which included a tribal of Petalangan region. Tribal customs territory covers an area Petalangan is Sorek, Ukui, Langgam and Tesso. This study aims to determine how the shape of social conflict in the region Tesso Nilo, knowing the communication strategy Tesso Nilo National Park Authority (BTNTN) in resolving conflicts, and knowing BTNTN efforts in economic development alternative for people Tesso Nilo region.This research use qualitative methods that present descriptive analysis. Data collective technic that we use is observation, interview and documentation. To obtained validity data in this research, use participation extension and triangulation. Subject of this research is BTNTN Chief, Forest Police (Investigation), Non Governmental Organizations (NGOs) Tesso Nilo Community Forum, People living in the area TNNP, The company (PT.RAPP).The result of this research showed the characteristics of conflict in the region TNNP form of cultural conflict, social conflict, economic conflict and conflict of laws. BTNTN communication strategy in dealing with social conflict in TNNP form analyst and research, policy formulation, program planning, and implementation of communication activities. BTNTN also receive feedback from the community and evaluation of the program activities. Communication Strategies Conflict Resolution BTNTN in the form of negotiation, mediation, facilitation and diplomacy, confrontation. Initiated the development of alternative economic development BTNTN on the utilization of natural honey, ecotourism program cooperation BTNTN and WWF Indonesia, the utilization of which there are many fish in the rivers in the area estates and TNNP and utilization of unused land.Key word: Communication strategy, Social conflict, Handling conflict, Economic development alternative , Tesso Nilo National Park Authority.